KONSTRUKSI PEMUNGUTAN RETRIBUSI PENYEDIAAN FASILITAS PASAR TRADISIONAL ANTARA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA BATAM DENGAN PENYEWA KIOS PASAR DITINJAU BERDASARKAN HUKUM PERDATA - Aulia Shaharani; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
An agreement is a law for the parties entering into it and the implementation of theagreement must not conflict with public order. The agreement must be adhered to if one partydoes not carry out the obligations that have been stipulated then that party has committed abreach of contract. Retribution is a regional levy as payment or certain services or gifts that arespecifically provided and/or given by the regional government for the benefit of individuals orentities.The problem that occurs in this thesis is that market traders have defaulted where marketstall tenants have not carried out one of their obligations as stipulated in the agreement. It hasbeen stipulated in the market stall rental agreement that Article 6 paragraph (2), in Article 7paragraph (1) Article 7 paragraph (5) In fact, in the field, traders still violate the agreementagreed upon by both parties. The method used in this research is a sociological type of research.The research was conducted at traditional markets managed by the Industry and Trade Office ofBatam City. The samples taken in this study were 10 people. Data collection techniques areinterviews and literature study.The results of this study are, the provisions stipulated in the market stall rentalagreement are in accordance with the law as well as the terms and elements of an agreement. theimplementation of the market stall rental agreement did not go well where there were still manymarket stall tenants who defaulted from 28 kiosk tenants, 21 kiosk tenants who violated the termsof the agreement. the efforts made by the relevant department of not fulfilling this achievementare by giving verbal reprimands and giving Warning Letters One to Three Warning Letters.Keyword:Default,Lease-Agreement,Retribution